Pengembangan Media Pembelajaran Berbasis Google Sites pada Materi Ikatan Kimia Bermuatan Multi Level Representasi Kimia - Veni Jumila Danin; Agus Kamaludin (Jurnal Penelitian Pendidikan IPA, 2023)
Website-based online learning media are needed by students to make it easier to understand multilevel representations of chemistry during the COVID-19 pandemic. This study aims to develop learning media based on google sites on chemical bonding material containing multilevel chemical representations and determine product quality. This media development adapts the 4-D development model, consisting of four stages: define, design, development, and disseminate. Quality assessment was carried out by material experts, media experts, chemistry teachers, and students responded. The research instrument was a product quality assessment sheet and student response sheets. The results showed that the quality of the media developed based on the assessment by the media obtained an ideal percentage of 97.5% in the excellent category, material experts obtained an ideal percentage of 85% in the excellent category, and chemistry teachers obtained an ideal percentage of 97% in the excellent category. Learning media based on google sites on chemical bonding material containing multilevel chemical representations also responded positively with a percentage of 93.75%. It can be concluded that the developed media is suitable for use in the learning process to improve students' multi-representation abilities on chemical bonding material.